The radical act of community storytelling : empowering voices in uncensored events - Starr, Penelope (Parkhurst Brothers Publishers Inc, 2017)
The Radical Act of Community Storytelling is everything it claims in the title. It is the story of a radical step of faith taken by Penelope Starr to open her life by bringing community storytelling to her community. It is the story of voices that often go unheard having the opportunity to speak and be heard. And it is about community building from start to finish ... including everything any radical would need to start a community storytelling organization in any community. --Adam Hostetter, Adult literacy educator, writer, and community storytelling producer.
Keywords: Storytelling -- Study and teaching.; Communities of practice.; Art de conter -- Étude et enseignement.; Communautés de pratique.; EDUCATION -- Elementary.; Communities of practice; Storytelling -- Study and teaching; Electronic books.; Electronic book.